Quantum Games Based Communication Protocols - O.G. Zabaleta; C.M. Arizmendi (Journal of Advances in Applied & Computational Mathematics, 2017)
Medium access control (MAC) and efficient spectrum allocation function particularly, are real challenges that wireless communications are facing nowadays and Dynamic Spectrum Access (DSA), enhanced with quantum computation techniques, is the most promising alternative. In such a context, we capitalize quantum games and quantum decisions strengths to design protocols that make classic communications more efficient. That is, we focus on protocols running on quantum devices whose input and output signals are classic. In this work we propose a quantum media access control (QMAC) that allows dynamic and fair spectrum allocation. Particularly, we point to two of the main DSA functions, which are Spectrum Sharing and Spectrum Allocation.